Strongyloides stercoralis e infecção pelo HIV : prevalência em pacientes HIV positivos em Vitória, Espírito Santo e revisão sistemática dos casos de estrongiloidíase grave em pacientes com HIV/AIDS - Gonçalves, Flávio Lofêgo (2011)
Introduction. Data on prevalence of Strongyloides stercoralis in HIV-infected patients are conflicting, both in Brazil and other countries. Despite the profound immunodeficiency, disseminated strongyloidiasis occurs incidentally in patients with HIV/AIDS, but the factors that trigger it are not known. Objectives (a) To search the prevalence of S. stercoralis in HIV-positive patients treated at Hospital CA Moraes in the period 2009-2011 and to compare with the prevalence in samples of the HIV negative patients at the same Hospital; (b) To investigate factors that may be associated with prevalence of Strongyloides, especially the excessive use of ethanol; (c) To review AIDS deaths in the Espírito Santo State between 1996 and 2010, to identify Strongyloides-related deaths; (d) To review the published cases of disseminated strongyloidiasis in AIDS patients, published since the beginning of the epidemic. Methods. Examination of stools, by the method of spontaneous sedimentation in the routine laboratory of the Hospital. Research habits and living conditions (use of footwear, type of occupation, use of treated water and sewerage and excessive use of ethanol (> 80 g / day of ethanol). Revision of deaths certificates between 1996 and 2010, to identify AIDS deaths and deaths related to Strongyloides. A systematic review of all cases of severe strongyloidiasis in AIDS patients, published in journals indexed in Pubmed, was performed. Results. The prevalence of S. stercoralis in 167 HIVpositive patients (13/167; 7,78%, 95% CI 3,7 to 11,7) did not differ significantly from the prevalence in a sample of HIV-negative patients at the same hospital, during the same period (9/220, 4.1%, 95% CI 1,5 to 6,8). In HIV-positive patients, alcoholics, the prevalence was significantly higher than in HIV positive non-alcoholics (respectively, 7/42, 16% and 6/123, 4,8%, p = 0.044) and than in a sample of non-alcoholics, HIV negative patients, at the same hospital (respectively 7/42, 16% and 26/491, 5.3% p = 0.010). The analysis of AIDS deaths revealed no deaths associated with Strongyloides among deaths occurred from 1996 to 2010 in the Espírito Santo State. Beyond severe immunodeficiency, the systematic review of published cases does not identify other frequent associated factors that would be associated with the spread of the parasite, explaining it in most cases. Conclusion: The prevalence of Strongyloides is similar in HIV positive and HIV negative patients at the same Hospital, but is significantly higher when chronic alcoholism is present. In the systematic review of published cases of Strongyloides hyperinfection or dissemination, beyond the immunodeficiency, no factor was reported in many cases, that would explain the dissemination of the parasite.